Persepsi Komitment Organisasi terhadap Produktivitas dan Dampaknya pada Organizational Citizenship Behavior pada PT. Perkebunan Sumatera Utara - Bima Shabha (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The aim of this research which done at PT. Perkebunan North Sumatera wasto determinedthe effected of organizational commitment on work productivity and the impact on organizational citizenship behavior. The population is employees who work in the company as many as 135 people, sampling with a census sample so that the number of samples is 135 respondents. Collecting data with surveys and data analysis techniques with class assumptions and hypotheses. The results showed that partially organizational commitment has a significant effect on work productivity and organizational citizenship behavior and work productivity has a significant effect on organizational citizenship behavior. Simultaneously organizational commitment and employee productivity have a positive and significant effect on organizational citizenship behavior. The correlation between organizational commitment and employee productivity is said to be sufficient on organizational citizenship behavior at PT. North Sumatra Plantation.